Effects of gamma irradiation in the antimicrobial activity of wild mushroom extracts - Fernandes, Ângela (2015)
The interest of mushrooms hás been increasing over time due to their potential in prevention or treatment of different diseases. Mushrooms have been reported for their anticancer, antiinflammatory, and immunosuppressive and antimicrobial properties. In particular, several authors reported the antibacterial activity of extracts prepared from different mushroom species [1]. In spite of these undeniable qualities, mushrooms are one of the most perishable products and tend to loose quality immediately after harvest. Irradiation is recognized as a safe and effective presen/ation method, being used worldwide to increase the shelf life of foods (e. g, fruits and vegetables, spices, grains, meat or seafood, aromatic and medicinal plants and spices) [2, 3]. In the present study, the antibacterial properties of methanolic extracts prepared from Boletus edulis Buli. and Hydnum repandum L. Fr., previously submitted to gamma irradiation, were assessed against clinicai isolates with different resistance profiles (two Gram negative bacteria; Escherichia coli and Proteus mirabilis, isolated from urine, and two Gram positive bactéria: MSSA- methicillin-sensitive Staphylococcus aureus, isolated from wound exudate and MRSA- methidllin-resistant Staphylococcus aureus, isolated from expectoration) from hospitalized patients in Local Health Unit of Mirandela, Northeast of Portugal. The fruiting bodies were collected in Trás-os-Mõntes (Northeast of Portugal) in November 2012. Gamma irradiation was performed in experimental equipment with four Co-60 sources at 1 and 2 kGy doses. The 1 kGy dose does not seem to be the preferable choice to treat B. edufe and H. repandum(which have a better response to the 2 kGy dose). Among the tested extracts, those obtained from B. ecfufe presented the highest activity against ali the tested bacterial. The antimicrobial activity of the mushroom extracts did not suffer significant changes that might compromise applying irradiation as a possible mushroom conservation technology. As a general conclusion, the 2 kGy should be considered as the best choice in terms of antimicrobial activity maintenance.